Progress and challenges in attaining global fisheries sustainability - Parma, Ana María (2019)
Global data on fish stock status are showing a turning of the tide in many fisheries, with marked reductions in fishing-induced mortality, followed in many cases by stock biomass recovery. These positive outcomes have resulted from stronger legal mandates to maintain fishing pressure at or below the levels that maximize long-term yields, and to implement rebuilding plans for overfished stocks. By in large these results provide empirical support to some basic principles of fisheries science that predict how fish abundance will change in response to fishing pressure controls. However, optimism in our ability to achieve fisheries sustainability targets globally needs to be tempered by the fact that these outcomes have been mainly documented for industrial fisheries in regions where there are effective management systems in place, able to: (i) collect and analyze data to assess stock status, (ii) adjust harvest controls in response to changes in abundance, and (iii) implement and enforce regulations. Such command-and-control approaches cannot be expected to work in small-scale fisheries and/or in regions with weak governance systems. While much attention has been focused on the fact that small-scale fisheries are typically data-limited, data limitations tend to go hand in hand with resource and capacity limitations that hamper all three components of the management system. More encompassing assessment and management frameworks have been proposed, but no quick fixes exist and approaches that have potential are highly context dependent. Thus, local successes cannot be scaled up simply by replication. Sustained efforts need to be allocated to building local capacity to collect and analyze information, and to identify strategies that may work given the specific constraints of each fishery. Tools and processes are being developed to support such engagements and to foster communities of practice that accelerate learning.